Religiosity, religion values, and science values in Northern Ireland and the Republic of Ireland - Hannah J. Kramer; Niamh McLoughlin; Kathleen H. Corriveau; Jocelyn B. Dautel (PLoS ONE, 2025)
We investigate the relation between religion and science in Northern Ireland and the Republic of Ireland. That is, we test the extent to which religiosity and valuing religion correspond with valuing science. We explore two contexts where religion and science are integral parts of society—Northern Ireland and the Republic of Ireland. As part of a larger study, participants (N = 739 adults living in Northern Ireland or the Republic of Ireland) reported their level of religiosity as well as responded to a survey that measured how much they value religion and science. In both contexts, religion and science were negatively related. In other words, participants who reported being more religious or who valued religion more tended to value science less. Findings are discussed in relation to the value of taking a global approach to studying religion and science as well as how this type of relation may contribute to polarization.